Potensi Pemanfaatan Air Danau Pascatambang di Wilayah Rumpin, Kabupaten Bogor, Jawa Barat - Maulana, Yuga; Tuheteru, Edy Jamal; Burhannudinnur, Muhammad; Hartami, Pantjanita Novi; Suliestyah; Alan, Muhammad Rallupy Meyraldo (Universitas Trisakti, 2024)
Mineral and coal mining has a significant impact on the surrounding environment. One of these impacts is the formation of post-mining lakes, often referred to as mine voids or pit lakes. The unavailability of rocks or the lack of cover material to backfill the mining area forms post-mining lakes. A post-mining lake forms when water fills the mine hole. In rock mining with the quarry method that reaches a certain depth, post-mining lakes are often formed because all the rocks are taken as products, so that no cover rock remains. The existence of post-mining lakes in several areas can have both positive and negative impacts. The positive impact is the sustainable use of post-mining lakes, for example, as a water resource for the surrounding community. Given the important role of post-mining lakes, it is necessary to conduct socialization with the community about how to utilize them. One area that requires attention is the Rumpin area, Bogor Regency, West Java, which has many post-mining lakes. We expect the community to gain insight and input regarding the potential utilization of water from post-mining lakes through this socialization activity. Thus, we can achieve the goal of sustainable mining while directly benefiting the surrounding community.